Is there diurnal variation of the vestibulosympathetic reflex: implications for orthostatic hypotension - Ray, Chester A. (American Physiological Society, 2013)
Incidences of adverse cardiac events and orthostatic hypotension are associated with diurnal variations. The primary purpose of the present study was to determine if the vestibulosympathetic reflex (VSR) follows a diurnal variation in humans. We hypothesized that the VSR would be attenuated at night based on the relation between melatonin and the VSR. Arterial blood pressure, heart rate, calf blood flow, and muscle sympathetic nerve activity (MSNA) were measured in nine healthy subjects (28 ± 1 yr, 5 men and 4 women) at rest and during head-down rotation. Each subject was tested during the day at 11:34 ± 13 and again at night 22:10 ± 5. MSNA was significantly decreased at night compared with day (8 ± 1 vs. 11 ± 2 bursts/min, respectively, P < 0.02). Heart rate and arterial blood pressure at rest were significantly increased at night compared with day (heart rate: 70 ± 4 vs. 66 ± 4 beats/min and mean arterial blood pressure: 91 ± 2 vs. 87 ± 1 mmHg, respectively). MSNA and hemodynamic responses to head-down rotation were not significantly altered at night compared with day (changes of 3 ± 1 bursts/min and 25 ± 6% for MSNA and calf blood flow, respectively). The data indicate that MSNA at rest decreases during the late evening hours and exhibits a diurnal variation, whereas the VSR does not. In summary, diurnal variation of orthostatic hypotension in humans does not appear to be associated with changes in the VSR and MSNA at rest.